The comfort level in breast cancer patients’ based on patients’ characteristics during the COVID-19 pandemic - Tuti Nuraini; Yushlihah Rofiati Yusuf; Shanti Farida Rachmi; Dewi Gayatri (Faculty of Nursing Universitas Padjadjaran, 2024)
Background: Comfort level in breast cancer patients is one of the most critical factors influencing patient’s treatment commitment. The COVID-19 pandemic has affected various sectors, especially health status. Objectives: This study aims to describe patients' comfort levels during the COVID-19 pandemic and to investigate the relationship between patients’ characteristics and comfort levels. Methods: This study involved 108 respondents using a consecutive sampling technique at one time (cross-sectional). The research instrument was Comfort Assessment Breast Cancer Instrument (CABCI). The data were analyzed using Chi-Square. Results: The results showed that the comfort level in this study is categorized as comfortable. The best comfort aspect is the environmental aspect and the least is the physical aspect. In addition, there are two variables related to comfort, treatment (p = 0.007; α = 0.05) and treatment room (p = 0.000; α = 0.05). The best comfort level was found in chemotherapy treatment and outpatient rooms. Patients feel comfortable with a neat, clean, conducive hospital environment and the implementation of health protocols. These aspects could effectively prevent the spread of COVID-19. Conclusions: The results of this study recommend nursing services to optimize all aspects of comfort, which could still be improved. Interventions that maintain or improve comfort will optimize patients’ health conditions.